Bentang dan Tanda-tanda Alam Serta Perubahan Nama Tumbuhan dan Hewan dalam Bratayuda Kawi Mawi Jarwa - Wisnurutomo, Adi (Jumantara: Jurnal Manuskrip Nusantara, 2024)
This article discusses the landscapes and natural signs contained in the text of Bratayuda Kawi mawi Jarwa, a jarwa text by R. Ng. Ranggawarsita whose writing uses a three-column commentary system. In general, the content of this text is only a jarwan or translation of Kakawin Bharatayuddha, so in terms of narrative the story in it is exactly the same as the kakawin form. The content of this text mostly discusses warfare, but it is not uncommon for poets to tell landscapes in the story. The landscape described by the poet is a forest landscape, besides that the poet also describes the natural signs that occur if a major event will or has occurred. On the other hand, from the three-column jarwa form used in this manuscript, the kakawin text and jarwa text can be compared so that it can be seen how the transformation of Javanese language from the old Javanese language to the new Javanese language, including the mention of plant and animal names. In its discussion, this article uses a philological approach, followed by an attempt to compare the texts between Kakawin Bharatayuddha and Bratayuda Kawi mawi Jarwa. With these approaches, this article analyzes several things, namely (1) landscapes in the text of Bratayuda Kawi mawi Jarwa, (2) signs of nature in the text of Bratayuda Kawi mawi Jarwa, and (3) transformation of plant and animal names. The results of the following research are (1) there are images of nature in the BKMJ text in the form of forest landscapes mentioned twice in the text, (2) there are two types of natural signs, namely natural signs as messengers and natural signs as depictions, (3) 49 plant names and 38 animal names are found, most of the names are still the same but there are also some differences.